The letters - Rice, Luanne. frey50; Monninger, Joseph (New York : Bantam Books, 2008)
Sam and Hadley West are both trying in their own ways to survive after the unthinkable loss of their only son in Alaska. For Sam, a sports journalist, acceptance means an arduous trek by dog sled across the bleak and beautiful arctic wilderness to find the place where Paul died. For Hadley, it means renting a benignly haunted, salt-soaked cottage off the Maine coast where she begins to paint again. Now, at opposite ends of the country, waiting for their divorce to be finalized, they begin to exchange letters by post, missives filled with longing and truths they've never before voiced, as they recall their marriage--its magic moments and its challenges--and begin to rediscover the reasons they fell in love in the first place.--From publisher description.
Keywords: Spouses; Bereavement; Adult children -- Death; Epistolary fiction